Connected Perfect Domination in Bipolar fuzzy graphs - Al-Kohily, Hameed; Shubatah, Mahioub M. Q. (IJRDO -JOURNAL OF MATHEMATICS, 2021)
In this paper we introduced and studied the concepts of connected domination γc(G) and tribal connected domination γtc(G) in bipolar fuzzy graphs. We determine the connected perfect domination number for some standard fuzzy graphs withsuitable examples. We investigated the relationship of γc(G) and γtc(G) with other knownparameters of G. Some bounds and some interesting results for the parameters are obtained. Further, we also obtain Nordhaus - Gaddum type results of γc(G). finally, thetribal connected perfect domination numberγtcp(G) for several classes of biploar fuzzygraphs are given with suitable example and obtain bounds for the same.